Practical modp̲erl - Bekman, Stas (O'Reilly, 2003)
Mod_perl embeds the popular programming language Perl in the Apache web server, giving rise to a fast and powerful web programming environment. Practical mod_perl is the definitive book on how to use, optimize, and troubleshoot mod_perl. New mod_perl users will learn how to quickly and easily get mod_perl compiled and installed. But the primary purpose of this book is to show you how to take full advantage of mod_perl: how to make a mod_perl-enabled Web site as fast, flexible, and easily-maintainable as possible. The authors draw from their own personal experience in the field, as well as the combined experience of the mod_perl community, to present a rich and complete picture of how to set up and maintain a successful mod_perl site. This book is also the first book to cover the "next generation" of mod_perl: mod_perl 2.0, a completely rewritten version of mod_perl designed for integration with Apache 2.0, which for the first time supports threads. The book covers the following topics, and more: Configuring mod_perl optimally for your web site Porting and optimizing programs for a mod_perl environment Performance tuning: getting the very fastest performance from your site Controlling and monitoring the server to circumvent crashes and clogs Integrating with databases efficiently and painlessly Debugging tips and tricks Maximizing security Written for Perl web developers and web administrators, Practical mod_perl is an extensive guide to the nuts and bolts of the powerful and popular combination of Apache and mod_perl. From writing and debugging scripts to keeping your server running without failures, the techniques in this book will help you squeeze every ounce of power out of your server. True to its title, this is the practical guide to mod_perl